A square lattice topology coordination network that exhibits highly selective C2H2/CO2 separation performance. (3rd November 2020) - Kumar, Naveen; Mukherjee, Soumya; Bezrukov, Andrey A.; Vandichel, Matthias; Shivanna, Mohana; Sensharma, Debobroto; Bajpai, Alankriti; Gascón, Victoria; Otake, Ken‐ichi; Kitagawa, Susumu; Zaworotko, Michael J.
Abstract: C2 H2 /CO2 separation is an industrially important process that remains challenging because of the similar physicochemical properties of C2 H2 and CO2 . We herein report that the new square lattice (sql ) coordination network [Cu(bipy‐xylene)2 (NO3 )2 ] n, sql‐16‐Cu‐NO 3, 16 = bipy‐xylene = 4, 4′‐(2, 5‐dimethyl‐1, 4‐phenylene)dipyridine, exists in at least three forms, as‐synthesised (α ), activated (α′ ) and hydrated (β ). The activated phase, sql‐16‐Cu‐NO 3 ‐α′, is an ultramicroporous material that exhibits high selectivity towards C2 H2 over CO2 as revealed by dynamic gas breakthrough experiments (1:1, C2 H2 /CO2 ) that afforded 99.87% pure CO2 in the effluent stream. The separation selectivity at 298 K and 1 bar, 78, is the third best value yet reported for C2 H2 selective physisorbents whereas the mid‐loading performance sets a new benchmark. The performance of sql‐16‐Cu‐NO 3 ‐α′ is attributed to a new type of C2 H2 binding site in which CH···ONO2 interactions enable moderately strong sorbent‐sorbate binding ( Q st (C2 H2 ) = 38.6 kJ/mol) at low loading. Conversely, weak CO2 binding ( Q st (CO2 ) = 25.6 kJ/mol) at low loading means that (Δ Q st )AC [ Q st (C2 H2 )– Q st (CO2 )] is 13 kJ/mol at low coverage and 11.4 kJ/mol at mid‐loading. Analysis of in situ powder X‐ray diffraction and modelling experiments provide insight into the sorption properties and high C2 H2 /CO2 separation performance of sql‐16‐Cu‐NO 3 ‐α′ . Abstract : Crystal engineering of square lattice (sql) coordination networks has resulted in a new layered ultramicroporous adsorbent, sql‐16‐Cu‐NO 3 ‐α′ . Thanks to its poor affinity to CO2 and optimal C2 H2 binding, sql‐16‐Cu‐NO 3 ‐α′ exhibits the rare combination of (a) high C2 H2 versus CO2 separation selectivity and (b) a new benchmark difference between the C2 H2 and CO2 adsorption enthalpies.